2005
DOI: 10.1152/ajprenal.00319.2004
|View full text |Cite
|
Sign up to set email alerts
|

The renal vascular response to ANG II injection is reduced in the nonclipped kidney of two-kidney, one-clip hypertension

Abstract: 1R) level in the nonclipped kidney of twokidney, one-clip hypertension (2K1C) has shown to be unchanged despite a high circulating angiotensin (ANG) II level. To examine the vasoreactive response to ANG II in this kidney, injections of ANG II into renal artery were performed 6 wk after clipping of the kidney and compared with normotensive controls. The renal blood flow (RBF) response to 2.5 ng ANG II was measured by a Transonic transit-time flowmeter, before and after indomethacin and candesartan treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
2
15
2
Order By: Relevance
“…Simultaneously, the mean arterial pressure (MAP) was also recorded and renal vascular resistance (RVR) was calculated based on RBF and MAP, using BOLUS program, customized software for the automated analysis of data. The experimental procedure has been described before (5). In short, anesthesia was induced by an intraperitoneal injection of pentobarbital sodium (65 mg/kg body wt) and the animals were placed on a servo-controlled heating table to keep the body temperature at 38°C.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, the mean arterial pressure (MAP) was also recorded and renal vascular resistance (RVR) was calculated based on RBF and MAP, using BOLUS program, customized software for the automated analysis of data. The experimental procedure has been described before (5). In short, anesthesia was induced by an intraperitoneal injection of pentobarbital sodium (65 mg/kg body wt) and the animals were placed on a servo-controlled heating table to keep the body temperature at 38°C.…”
Section: Animalsmentioning
confidence: 99%
“…ANG II in the nonclipped kidney of 2K1C-hypertensive has been shown before (5). It might be due to increased endogenous ANG II concentration with reduced number of available AT1 receptors and attenuated renal vascular response as a result.…”
mentioning
confidence: 92%
“…Studies from our laboratory recently showed decreased responses in RBF to renal ANG II injections in the nonclipped kidney of 2K1C compared with control animals, although the preglomerular AT 1a R levels ex vivo seem to be unchanged (2). The reason for this apparent dysregulation is unclear, and further investigations are needed.…”
mentioning
confidence: 91%
“…This results in elevated plasma renin activity and an increase in blood pressure mediated by facilitated conversion of AngI to AngII [45]. Circulating levels of renin and AngII are transiently elevated during the initial acute stage, subside during the intermediate stage, and then once again increase and remain elevated during the chronic maintenance stage.…”
Section: Goldblatt Hypertension Modelmentioning
confidence: 99%
“…These investigators also reported that isolated glomeruli from the groups with increased APA expression metabolized AngII to a greater extent. Recently, Bivol and colleagues [45] have noted that in the established stage of the Goldblatt hypertensive model the vascular response to AngII injection in the non-clipped kidney was substantially reduced despite normal vascular levels of AT 1 R expression. This could be due to increased APA levels as reported by Wolf et al [48,49].…”
Section: Goldblatt Hypertension Modelmentioning
confidence: 99%